Exploring Students' Difficulties in Comprehending English Reading Texts at SMP Muhammadiyah Limbung - Siti Nuralimah; Ahmad Talib; La Sunra (ARRUS Journal of Social Sciences and Humanities, 2023)
The aims of this research are to explore students’ difficulties in comprehending English reading texts and to discover the causing factors of students’ difficulties in comprehending English reading texts. This research is a qualitative descriptive method. Participants of this research were students of class VIII. 3 at SMP Muhammadiyah Limbung. The instruments used in this research were reading comprehension test and interview. The reading comprehension test was administered to 26 students in class VIII.3 in form of an essay test to collect the data regarding students’ difficulties based on the mistakes they made in answering the test. The researcher chose 15 students as participants in the interview. The interview was used as the supporting data from the reading comprehension test and to identify the causing factors of students’ difficulties. The results of the reading comprehension test and interview showed that there were five difficulties students experienced in comprehending English reading texts. The difficulties that they experienced were difficulty in comprehending the main idea, difficulty in understanding vocabulary, difficulty in understanding references, difficulty in understanding inferences, and difficulty in understanding detailed information. The causing factors of students’ difficulties in comprehending English reading texts are divided into two factors, namely internal and external factors. Internal factors include limited vocabulary knowledge, lack of fluency, lack of familiarity with the subject matter, difficulty level of the text (readability), inadequate use of effective reading strategies, weak verbal reasoning, problems with information processing, and problems in recalling after reading. External factors include home environment and school environment.